Force and marriage the criminalisation of forced marriage in Dutch, English and international criminal law - Haenen, Iris, 1986- (Cambridge : Intersentia, 2014)
This text provides a comparative perspective on the criminalization of forced marriage, focusing on the question of whether, and, if so how, the practice of forced marriage should be criminalized under Dutch and international law. After offering a thorough description of the phenomenon of forced marriage in and outside of conflict situations, a synthesized doctrinal foundation for criminalization on the national and international level is presented.
Consensus facet nuptials -- Forced marriage in the Netherlands and England -- Forced marriages in conflict situations -- National criminalization -- International criminalization -- Comparing national and international criminalization -- Dutch and English law and forced marriage -- International criminal law and forced marriage -- Two-level legal comparison -- The criminalization of forced marriage under Dutch law and in the Rome Statute
Includes bibliographical references (pages 373-389) and index.
Keywords: Forced marriage; Marriage law; Marriage law -- England; Marriage law -- Wales; Marriage law -- Netherlands; Forced marriage -- England; Forced marriage -- Wales; Forced marriage -- Netherlands